Prognostic significance of TRAIL death receptors in Middle Eastern colorectal carcinomas and their correlation to oncogenic KRAS alterations - Hussain Azhar R; Al-Dayel Fouad; Alhomoud Samar; Ashari Luai H; Abduljabbar Alaa; Al-Sanea Nasser; George Thara; Qadri Zeeshan; Abubaker Jehad; Prabhakaran Sarita E; Bavi Prashant; Uddin Shahab; et al. (Molecular Cancer, 2010)
Abstract Background Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a member of the tumour necrosis factor cytokine family that induces apoptosis upon binding to its death domain containing receptors, TRAIL receptor 1 (DR4) and TRAIL receptor 2 (DR5). Expression of TRAIL receptors is higher in colorectal carcinoma (CRC) as compared to normal colorectal mucosa and targeted therapy with TRAIL leads to preferential killing of tumor cells sparing normal cells. Methods We investigated the expression of TRAIL and its receptors in a tissue microarray cohort of 448 Middle Eastern CRC. We also studied the correlation between TRAIL receptors and various clinico-pathological features including key molecular alterations and overall survival. Results CRC subset with TRAIL-R1 expression was associated with a less aggressive phenotype characterized by early stage (p = 0.0251) and a histology subtype of adenocarcinomas (p = 0.0355). Similarly CRC subset with TRAIL-R2 expression was associated with a well-differentiated tumors (p < 0.0001), histology subtype of adenocarcinomas (p = 0.0010) and tumors in left colon (p = 0.0009). Over expression of pro apoptotic markers: p27KIP1 and KRAS4A isoforms was significantly higher in CRC subset with TRAIL-R1 and TRAIL-R2 expression; TRAIL-R1 expression was also associated with cleaved caspase-3(p = 0.0011). Interestingly, TRAIL-R2 expression was associated with a microsatellite stable (MS--S/L) phenotype (p = 0.0003) and with absence of KRAS mutations (p = 0.0481). Conclusion TRAIL-R1 expression was an independent prognostic marker for better survival in all CRC samples and even in the CRC group that received adjuvant therapy. The biological effects of TRAIL in CRC models, its enhancement of chemosensitivity towards standard chemotherapeutic agents and the effect of endogenous TRAIL receptor levels on survival make TRAIL an extremely attractive therapeutic target.